Optimal Management of High-Voltage Line Congestions Using Power Source Redispatching - Paweł Pijarski; Adrian Belowski; Ľubomír Beňa; Tomasz Binkowski; Bartłomiej Mroczek (Applied Sciences, 2025)
The increasing integration of renewable energy sources (RESs) reduces dependence on conventional generators, thereby minimizing the negative environmental impact of fossil fuels. The distributed location of RESs also affects the voltage profiles (voltage values in network nodes) and reduces power losses. The growing number of RESs connected to the network increases the total installed power in the sources in the power system. This contributes to the periodic excess of generated power. It creates the need to limit generation in conventional power plants and to switch off some RESs. This article proposes an original methodology for optimally managing overloads of high-voltage power lines. The combination of the power flow tracking method and metaheuristic optimization allows for the effective elimination of line overloads. The aim of the calculations is to find the optimal power distribution in the selected sources, which provide minimal power limitation. As a result, this means a minimal reduction in the total generation in RESs. In this way, the effect of eliminating line overloads is achieved at the lowest possible cost of power redispatching. On the basis of the IEEE 118 bus test network, computational cases are considered, which are examples of emergency states.